Análise dos efeitos da adição de catio3 em lafeo3 e a aplicação de soluções sólidas desses materiais como antenas ressoadoras dielétricas - Azevedo, Lucas Oliveira de (2021)
With the advancement of technology and telecommunications, becomes more necessary the effort for the research and development of suitable antennas to meet the various technological demands. In this environment, compact, efficient antennas having high thermal stability are required, thus, dielectric resonator antennas (DRAs) are shown to be a viable option. The objective of this work is to study dielectric solid solutions samples of lanthanum ferrite (LaFeO3 or LFO) and calcium titanate (CaTiO3 or CTO): LFO(1-m)CTO(m), for different weight fractions m, as resonators for dielectric resonator antennas operating in HEM11δ mode in the microwave range of frequencies, due to the scarcity of studies of these materials in this range. For this, the theoretical resonance frequencies of the samples were calculated based on the equations available in the literature and measurements of their dielectric and antenna parameters were performed to observe the behavior of the samples as electromagnetic energy radiators; soon after, simulations were performed for comparation with the measured results. For the DRAs, it was possible to obtain resonance frequencies in the C, S and L bands of the frequency spectrum, having broadside and directional radiation diagram, with good gain in addition to good impedance match, operating properly. Furthermore, it was found that as the mass fraction m increases, the resonant frequency tends to reduce its value and that antennas with a smaller mass fraction tend to be more efficient. It was also possible to observe the counterclockwise rotation of the impedances pattern in the Smith chart for some of the resonators in two different setups